Answer:
part A: expression 1: 6(8m+2)
expression 2: 6m+12+42m
Part B: 6(m+2+7m)= 6(8m+2)
combine like terms is 6(m+2+7m), so it is 6(2+8m) or 6(8m+2)
6(8m+2)= 6(8m+2)
Part C: 6m+12+42m=6(m+2+7m)
m=0
6(0+2+7(0))=6(0)+12+42(0)
6(2)= 12
12=12
Answer:
t=382
Step-by-step explanation:
The square root of 15 is irrational.
If you want a answer for this you need to show the graph to us
To understand this question, we need some knowledge on radioactive decay. This type of nuclear decay is called a beta decay
<h3>Beta Decay</h3>
This is the process where a radioactive material is fired or naturally emits a beta particle which is equivalent to the lose of an electron and spontaneously becomes an entirely different element.
The participating actors in this nuclear reaction are
This is the decay process of helium particle in which it became a lithium particle and emitted an electron in the process.
Learn more on beta decay here;
brainly.com/question/9615302
#SPJ4